Technological Challenges in Online Learning During Covid-19 Pandemic: A Focus Group Discussion Exploring Nursing Students’ Perspectives - Evelyn Tambunan (Universitas Pahlawan Tuanku Tambusai, 2023)
In nursing education, the use of technology can have a significant influence on the online learning process. However, in the Covid-19 pandemic era of nursing education, many challenges in online learning were encountered. Within this context, the present study aimed to explore undergraduate nursing students’ perceptions regarding the technological challenges in online learning during Covid-19 pandemic. A qualitative study was conducted using zoom focus group discussions synchronously with the help of a discussion guide consisting of five open-ended questions. Overall, 34 nursing students were recruited using a maximum variation sampling technique; these students then participated in four focus group discussions. All interviews were recorded, transcribed verbatim, and analyzed for thematic contents using the standard created by Kyngas content analysis framework. A thematic content analysis yielded four core themes: (1) technical issues, (2) technology cost, (3) inexperience in ICT, (4) clinical learning issues. The seven sub-theme emerged: (1) incompatibility technological devices, (2) unstable internet connectivity, (3) purchase adequate technology devices, (4) purchase additional study quota, (5) students’ new experience, (6) faculties’ new experience, (7) inadequate clinical learning platform. Technological challenges were encountered in online learning during Covid-19 pandemic. This represents a significant picture perceived by nursing students. The challenges in online nursing education should be rigorously evaluated to monitor its effectiveness.